Analisis Kebutuhan Media Pembelajaran Fisika SMA Berbasis Teknologi dan Non Teknologi Pada Era Revolusi Indsutri 4.0 - Fitriyah, Lailatul; Kholiq, Abd (IPF: Inovasi Pendidikan Fisika, 2024)
Technological developments in the era of the increasingly rapid industrial revolution 4.0 have a major influence on all areas of life, both social, religious and educational. In the field of education, increasingly rapid technological developments influence the learning media applied in learning. The aim of this research is to analyze learning media needs in the application of physics learning using quantitative descriptive analysis, so that by analyzing media needs more varied and innovative learning media can be developed so that physics learning will be more meaningful and in line with current developments. This research was conducted at one of the MA in Gresik. The population in this study was 310 students and three physics teachers. Analysis of learning media needs based on the results of questionnaires given to students and interviewa with physics teachers. Based on the results of research that has been carried out, the learning media applied in physics learning based on Technology Information (IT) media which is most often applied in the learning process, namely the use of Power Point Text (PPT) obtained a percentage of 59,46%, PhET Simulation 8,11%, e-Book PDF 8,11% and quizizz usage 24,32%. Physics learning media apllying Non Technology Information (Non IT) whiteboard media obtained a percentage of 80,58%, printed textbooks 16,68% and the use of experimental KITs 2,74%. Based on the research conducted, it can be said that IT and Non-IT based learnng media applied in physics learning are still less varied and interactive and monotonous, so they are less varied and interesting in learning. Keywords: Instructional media, industrial revolution, education